2013
DOI: 10.7314/apjcp.2013.14.5.2959
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment Strategies on Local Control and Survival in Uterine Carcinosarcomas in Turkey

Abstract: Background: The purpose of this study was to determine the clinical characteristics, patterns of recurrence and survival outcomes in patients with uterine carcinosarcomas treated in our institution. Materials and Methods: Records of 26 patients diagnosed between 2007 and 2011 with uterine carcinosarcoma were retrospectively evaluated for demographic features, tumor characteristics, treatment regimens and patient outcomes in terms of DFS and OS Results: Median age was 61 (range 43-78). 10 patients (38%) had sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Reported 2-year DFS and 2-year OS ranged between 26% to 58% and 48% to 64%, respectively. 17,18 These rates were reported 27% for 5-year DFS and 30% to 60% for 5-year OS. 18Y20 In this study, 3-year DFS and 3-year OS were 42.7% and 59.2%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Reported 2-year DFS and 2-year OS ranged between 26% to 58% and 48% to 64%, respectively. 17,18 These rates were reported 27% for 5-year DFS and 30% to 60% for 5-year OS. 18Y20 In this study, 3-year DFS and 3-year OS were 42.7% and 59.2%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that the response rate of children with relapsed or resistant WT to a combination of carboplatin, ifosfamide, and etoposide, at the maximal tolerated dose of 635 mg/m 2 for carboplatin, is associated with a CR rate of 32% and a total response rate of 63% (Kung et al, 1993;Kung et al, 1995). In the field of cancer chemotherapy including in the treatment of WT, carboplatin is a common choice (Akkuzu et al, 2013;Bag et al, 2013;Butthongkomvong et al, 2013;Fu et al, 2013;Khemapech et al, 2013;Kucukoztas et al, 2013;Natukula et al, 2013;Oranratanaphan et al, 2013;Ozdemir et al, 2013;Zhang et al, 2013;Pitakkarnkul et al, 2013). It was reported that carboplatin, at a dose of 550 mg/m 2 every 3 weeks, as a single drug resulted in a response rate of 53% in children with relapsed WT (de Camargo et al, 1994).…”
Section: Introductionmentioning
confidence: 99%